Effects of the number of ethylene glycol units on the efficacy of novel complex I inhibitor 9bw - Kazuaki Sekimoto; Hanaka Kinjo; Mizuki Murakami; Akiko Ohashi; Rei Fukui; Eri Nagasaki-Maeoka; Yoshinori Inagaki; Tadateru Takayama; Kazuhiro Ikeda; Ken-ichi Takayama; Satoshi Inoue; Motonori Tsuji; et al. (Biochemistry and Biophysics Reports)
4′-Iodobiphenyl nonaethylene glycol ether (9bw) is a novel small molecule, composed of a biphenyl unit and 9 ethylene glycol (EG) units. Recently, we found that 9bw induces apoptosis in cancer cells by inhibiting mitochondrial respiratory complex I (CI) and accordingly reducing cellular ATP level. In addition, 9bw shows little effect on normal cells, suggesting that 9bw is a potential antitumor agent with few adverse effects. However, the exact molecular mechanisms by which 9bw acts on CI are still elusive. To clarify the molecular structure critical for 9bw′s function, we tested the function of 9bw analogues on human oral squamous cell carcinoma lines HSC4 and Ca9-22. The analogues were 4-hydroxy-4′-iodobiphenyl (HIOP), I-BP-EG3, I-BP-EG6, and I-BP-EG12 containing 0, 3, 6, and 12 EG units, respectively. Our results demonstrated that I-BP-EG6 and I-BP-EG12 inhibited CI to a similar extent as 9bw, whereas I-BP3 and HIOP showed no effect on CI activity. These observations indicate that the number of EG units is crucial for the activity of 9bw and its analogues. As high-performance liquid chromatography (HPLC) analysis demonstrated that both HIOP and I-BP-EG3 could be incorporated into mitochondria abundantly, the number of EG units probably affects CI inhibitory function of 9bw and its analogues rather than their efficacy to enter cell and mitochondria.